Development Of A Malaysian Preschoolers’ Esl Reading Assessment Instrument To Screen Reading Readiness - Ooi, Choon Lean (2019)
The ability to read is one of the most important skills that young children undertake in order to begin their academic endeavours. Students enter classrooms with diverse backgrounds and skills in literacy. Due to the various diversities, it was necessary to design a standard assessment to screen the reading readiness and reading abilities of preschool students before they further their education in Primary school. The main objective of this paper was to construct a generic reading test instrument which would be valid, reliable and practical that can discriminate and sort students into specific reading abilities. The generic reading test consists of 40 items in line with English reading requirements in the National Standard Preschool Curriculum. The test was then piloted and the data collected from the test would be used to develop the cut score for each level and a set of written descriptors that would describe the preschooler’s reading proficiency. Data collected could be used to profile preschool students according to able readers, somewhat able readers and as yet unable to read preschoolers. The administration of the generic test involved 350 preschool students from 18 preschools annexed to primary schools in Penang and Seberang Perai. The findings revealed that the majority of preschoolers in Penang and Seberang Perai have acquired the basic skills in reading readiness but will need more encouragement to develop further reading skills. The findings will provide educators with useful information so as to expand and develop relevant teaching materials for preschools and there will be continuity when students begin their education in Primary school.